Construction of SIRT1 gene shRNA lentivirus vector and its effect on the proliferation of breast cancer cells - Yue, Yanbo; He, Lili; Tian, Mi; Li, Xin (Cellular and Molecular Biology, 2020)
Current experiment aimed to investigate the construction of the SIRT1 gene shRNA lentivirus vector and its effect on proliferation of breast cancer cells. Altogether 80 cases of breast cancer tissues and 80 cases of normal adjacent tissues were collected. qPCR was used for detecting SIRT1 expression. Western blot was used to detect the expression of EMT marker protein. The effect of lentivirus infected sh-SIRT1 on the cell biological function of SK-BR-3 and MDA-MB-231 cells was detected. MTT assay was used to detect cell activity, Transwell cell was used to detect cell invasion and migration, and cell apoptosis detected by flow cytometry. Compared with normal tissues adjacent to cancer, the expression of SIRT1 in cancer tissues increased significantly. Compared with human breast epithelial cells (MCF 10A), SIRT1 expression in breast cancer cells (MDA-MB-231, SK-BR-3) increased significantly. The above results showed that SIRT1 was significant greatly expressed in breast cancer. Compared with the sh-Control group, the cell activity, invasion and migration of the sh-SIRT1 group were enhanced, while cell apoptosis was weakened. In the sh-SIRT1 group infected by lentivirus, cell activity, cell invasion and migration decreased, while cell apoptosis increased. Compared with sh-Control, the expression of Î±-catenin, PTEN and E-cadherin in the sh-SIRT1 group in SK-BR-3 and MDA-MB-231 cells was down-regulated, while the expression of N- cadherin, Î²-catenin and Vimentin was up-regulated. Compared with sh-Control, the expression of Î±-catenin, PTEN and E-cadherin in the sh-SIRT1 group infected by lentivirus was up-regulated, while the expression of N- cadherin, Î²-catenin and Vimentin was down-regulated. To sum up, SIRT1 is highly expressed in breast cancer cells. The proliferation of breast cancer cells was inhibited after lentivirus infection with sh-SIRT1.